2020
DOI: 10.1002/pbc.28749
|View full text |Cite
|
Sign up to set email alerts
|

Primary caregiver decision‐making in hematopoietic cell transplantation and gene therapy for sickle cell disease

Abstract: Background: Improved outcomes and the availability of clinical trials of hematopoietic cell transplantation (HCT) from alternate donors and genetically modified autologous hematopoietic progenitor cells have expanded the applicability of HCT for sickle cell disease (SCD). To understand the perspective of primary caregivers exploring HCT in the current milieu, we asked the research question "What motivates primary caregivers to decide to consider HCT and to seek, and to attend, an HCT consultation?" Procedures:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…Some physicians expressed a desire to see QoL pre-HCT and the anticipated impact of HCT on QoL in the risk prediction model of the decision support tool. Studies of decision-making by patients suggest that patients and families consider QoL important in decision-making about HCT [ 18 , 23 - 27 ]. Recent clinical trials have suggested that HCT can improve QoL after HCT [ 34 - 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some physicians expressed a desire to see QoL pre-HCT and the anticipated impact of HCT on QoL in the risk prediction model of the decision support tool. Studies of decision-making by patients suggest that patients and families consider QoL important in decision-making about HCT [ 18 , 23 - 27 ]. Recent clinical trials have suggested that HCT can improve QoL after HCT [ 34 - 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The availability of novel treatments, as well as the increased willingness of physicians and patients to consider HCT, may contribute to the increasing uptake of this treatment [ 20 - 22 ]. Previous studies have investigated the decision-making process and preferences of patients and families considering HCT [ 18 , 23 - 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…They report that patients learned about curative options from social media and news. 42 Caregivers sought consultation owing to their child’s diminished quality of life, recent complications, anxiety about future difficulty, or an imminent major medical decision. Gene therapy was seen as a less invasive and more acceptable treatment option as compared to HSCT.…”
Section: Qualitative Studiesmentioning
confidence: 99%
“…However, a par ent may also con sider other trade-offs such as the out comes of HCT in child hood vs the poten tial for mor bid ity and mor tality in adult hood, HRQOL with or with out HCT, and cura tive HCT vs chronic GVHD, infer til ity, car dio vas cu lar risk, and sub se quent malig nancy. 28 How fam i lies resolve these deci sional trade-offs is likely to be highly indi vid u al ized and depen dent on sev eral factors unique to the cir cum stances of the patient and fam ily. To assist the hema tol o gist in the con ver sa tion with the fam ily of a young child with SCD who has an HLA-iden ti cal sib ling, we summa rize the avail able evi dence as answers to crit i cal ques tions that may arise in the minds of patients and their care giv ers as they con tem plate HCT.…”
Section: The Risk-ben E Fit Trade-off In Hct For Scdmentioning
confidence: 99%